2012
DOI: 10.1007/s00381-011-1670-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of vagus nerve stimulation in children and adolescents with drug-resistant epilepsy

Abstract: Vagus nerve stimulation therapy is a safe and effective adjunctive treatment for children and adolescents of all ages with drug-resistant epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
(45 reference statements)
0
24
0
2
Order By: Relevance
“…Sixteen Class III studies were identified regarding the efficacy of VNS for seizure treatment in children (see table e-1 for study details). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This group of studies included 2 reports of patients with tuberous sclerosis 16,17 and one report of patients with Dravet syndrome. 18 Ten of 16 studies included subjects through age 18 18 One study of 11 patients with tuberous sclerosis had a mean age of 14, and the range of ages included was 2-35, with 2 subjects older than 19 (27 and 35).…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…Sixteen Class III studies were identified regarding the efficacy of VNS for seizure treatment in children (see table e-1 for study details). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This group of studies included 2 reports of patients with tuberous sclerosis 16,17 and one report of patients with Dravet syndrome. 18 Ten of 16 studies included subjects through age 18 18 One study of 11 patients with tuberous sclerosis had a mean age of 14, and the range of ages included was 2-35, with 2 subjects older than 19 (27 and 35).…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…[17,21] Other common adverse events of VNS, that were not present in our group of patients include bleeding and infection from the surgery, dyspnea, transitory hypotension, ventricular asystole, dyspnea, dyspepsia, dysphagia, vomiting, pharyngitis, headache and psychosis. Nearly two thirds of 57 patients in the study of MajkowskaZwolińska et al [7] experienced no adverse events specifically related to VNS. So we agree that this treatment is a safe option with minor side effects and injuries.…”
Section: Discussionmentioning
confidence: 91%
“…A slight decrease of antiepileptic drugs was reported in another study by Majkowska-Zwolińska et al [7] whereas no significant reduction after VNS implantation over one year follow up was stated by Elliott et al [20] The reduction in usage of antiepileptic drugs is very important from clinical point of view, since chronic use of these drugs may cause several side effects which contributes the impairment of quality of life in these patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations